STABILITY IN TWO-STAGE STOCHASTIC INTEGER PROGRAMMING - Esther Nababan (Proceedings of ICMSA, 2005)
There is a large number of different approaches for formulating andsolving optimization problems under uncertainty. In applications, one isusually faces incomplete information on probability measure u.Numerical attemps has been made mostly rely on approximating u by"simpler" measures. This paper presents overview of stability of twostageStochastic Integer Programming model under perturbations of theintegrating probability measure u.Keywords : stochastic programming, complete integer recourse,Simple integer recourse, stability, probability measure.